Linking Land use/Cover and Fossil Energy Consumption to Detect the Carbon Footprint Changes in the Yangtze River Delta, China - Xia, Yan; Pei, Fengsong (Journal of Environmental Science and Engineering Technology, 2022)
Fossil energy consumption is considered as an important source of carbon emission worldwide. As one of ecological footprint methodology, carbon footprint is emerging as an effective tool for carbon emission management, especially that from fossil energy consumption. Taking one of the most developed regions in China, the Yangtze River Delta as a case study, this paper analyzes carbon footprint of fossil energy consumption through productive lands by explicitly addressing spatial changes of land use/cover. The impacts of land use change on the carbon footprint are then assessed by coupling changes in land use/cover and fossil energy consumption. The results show that carbon footprint from energy consumption in the Yangtze River Delta increased from 322531 km2 in 2001 to 862924 km2 in 2013. Despite the fact that productive lands (i.e., forest and grasslands) were rising, the carbon footprint was still in deficit, about 831873 km2 in 2013. According to scenario analysis, carbon footprint is expected to reach 2572837 km2 in 2025 in the condition of ecological protection, 2604049 km2 in the condition of business as usual and 2609125 km2 in cultivated land protection. The results propose urgent policy measures to protect productive lands to reduce the ecological pressure of carbon emissions from energy consumption.